Differential composition of the pulmonary microbiome in HIV-positive versus HIV-negative patients with Pneumocystis jirovecii - Chang-Run Zhang; Mei Wang; Lei Wang; Li Liu; Yi-Dan Shen; Rui-Fang Chen; Shuai Ren; Wei-Zhong Jin; Hai-Cheng Tang; Qing-Guo Wu (PLoS ONE, 2025)
Pneumocystis jirovecii is frequently detected in HIV patients and individuals with compromised immune function. The clinical outcomes of these two groups differ significantly, yet the underlying reasons remain unclear, with limited studies addressing this issue. This study investigates the alterations in the pulmonary microbiota of HIV-positive and non-HIV patients following pneumocystis jirovecii infection.Collect bronchoalveolar lavage fluid from patients with HIV and non HIV infected Pneumocystis jirovecii, and compare the differences in pulmonary microbiota between the two groups.In total, 77 patients with pulmonary infection that had next generation sequencing performed on their bronchoalveolar lavage fluid and confirmed pneumocystis jirovecii infection were recruited in our study. Of the 77 patients with pneumocystis jirovecii infection, 52 were infected with HIV, and 25 were uninfected.Our findings indicate that HIV-positive patients exhibit a more diverse microbiota, predominantly characterized by viral co-infections. Specifically, 88.5% of HIV-positive patients experienced viral co-infections, primarily involving herpes viruses, followed by bacterial (61.5%) and fungal (40.4%) co-infections. In contrast, non-HIV patients predominantly exhibited bacterial co-infections (72%), followed by viral (52%) and fungal (36%) co-infections. By analyzing the next generation sequencing data of both groups, we identified statistically significant differences in viral infections (p < 0.001), while no significant differences were observed for bacterial or fungal infections. Furthermore, among the background bacteria detected via next generation sequencing in both patient groups, 22 microbial species were commonly present. Notably, Leptospiral virus, Rosette fungus, and Actinomycetes were detected at higher frequencies in HIV-infected pneumocystis jirovecii patients, with statistically significant differences.Through comparing the pulmonary microbiota profiles of HIV-positive and non-HIV patients post-pneumocystis jirovecii infection, we uncovered distinct differences between the two groups, which may hold implications for guiding subsequent treatment strategies and improving clinical outcomes.